Unlocking Human Potential: A Literature Review on HR Challenges and Innovations in SME Entrepreneurship - Abas, Mohamad Fathanudin; Pardiman, P.; Supriyanto, S. (Jurnal Manajemen Bisnis, 2024)
This literature review explores the intricacies of human resource management (HRM) in small and medium-sized enterprises (SMEs), focusing on the unique challenges and innovative practices that characterize HR operations within this sector. The primary objective of this study is to synthesize existing literature to understand how SMEs manage their human resources amidst resource constraints and competitive pressures from the global talent market. Employing a qualitative research methodology, this review meticulously analysed scholarly articles, industry reports, and case studies to develop a comprehensive understanding of the current HR landscape in SMEs. The findings reveal that SMEs frequently grapple with issues such as limited financial and human resources, difficulties in attracting and retaining talent, compliance with complex employment laws, and the integration of technology in HR practices. Despite these challenges, SMEs often adopt flexible and innovative HR approaches that leverage their agility and close-knit organizational cultures to enhance employee engagement and organizational loyalty. Theoretical frameworks like the Resource-Based View, Psychological Contract Theory, and Social Exchange Theory provide valuable insights into effective strategies for managing human resources in SMEs. The study underscores the importance of strategic HR management in leveraging human capital as a key asset for competitive advantage. It also highlights the critical role of technology in streamlining HR operations, suggesting that SMEs can significantly benefit from embracing HR innovations to overcome inherent limitations and foster sustainable growth.